Rationale and design of the quantification of myocardial blood flow using dynamic PET/CTA-fused imagery (DEMYSTIFY) to determine physiological significance of specific coronary lesions. - AlBadri, Ahmed; Piccinelli, Marina; Cho, Sang-Geon; Lee, Joo Myung; Jaber, Wissam; De Cecco, Carlo N.; Samady, Habib; Koo, Bon-Kwon; Bom, Hee-Seung; Garcia, Ernest V. (Journal of Nuclear Cardiology, 2020)
Background: Coronary physiology assessments have been shown by multiple trials to add clinical value in detecting significant coronary artery disease and predicting cardiovascular outcomes. Fractional flow reserve (FFR) obtained during invasive coronary angiography (ICA) has become the new reference standard for hemodynamic significance detection. Absolute myocardial blood flow (MBF) quantification by means of dynamic positron emission tomography (dPET) has high diagnostic and prognostic values. FFR is an invasive measure and as such cannot be applied broadly, while MBF quantification is commonly performed on standard vascular territories intermixing normal flow from normal regions with abnormal flow from abnormal regions and consequently limiting its diagnostic power.Objective: The aim of this study is to provide physicians with reliable software tools for the non-invasive assessment of lesion-specific physiological significance for the entire coronary tree by combining PET-derived absolute flow data and coronary computed tomography angiography (CTA)-derived anatomy and coronary centerlines.Methods: The dynamic PET/CTA myocardial blood flow assessment with fused imagery (DEMYSTIFY) study is an observational prospective clinical study to develop algorithms and software tools to fuse coronary anatomy data obtained from CTA with dPET data to non-invasively measure absolute MBF, myocardial flow reserve, and relative flow reserve across specific coronary lesions. Patients (N = 108) will be collected from 4 institutions (Emory University Hospital, USA; Chonnam National University Hospital, South Korea; Samsung Medical Center, South Korea; Seoul National University Hospital, South Korea). These results will be compared to those obtained invasively in the catheterization laboratory and to a relatively novel non-invasive technique to estimate FFR based on CTA and computational fluid dynamics.Conclusions: Success of these developments should lead to the following benefits: (1) eliminate unnecessary invasive coronary angiography in patients with no significant lesions, (2) avoid stenting physiologically insignificant lesions, (3) guide percutaneous coronary interventions process to the location of significant lesions, (4) provide a flow-color-coded 3D roadmap of the entire coronary tree to guide bypass surgery, and (5) use less radiation and lower the cost from unnecessary procedures.Trial Registry: The DEMYSTIFY study has been registered on ClinicalTrials.gov with registration number NCT04221594.